2017
DOI: 10.15414/jmbfs.2017.7.1.32-36
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium Wilt Disease of Tomato: Screening for Resistance and in-Vitro Evaluation of Botanicals for Control; The Nigeria Case

Abstract: Fusarium wilt disease of tomato is caused by Fusarium oxysporum f. sp. lycopersici and is a limiting factor to tomato production in Nigeria. The objectives of this study were to screen tomato varieties commonly cultivated in Nigeria to determine their host resistance status to F. oxysporum, identify fungi species associated with tomato plants showing Fusarium wilt symptoms and the in-vitro evaluation of aqueous and methanol extracts of four botanicals for bioactivity. Symptomatic sample plants were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…The presence of antifungal substances in the extracts could be responsible for the observed inhibition of radial growth, as well as possible inhibition of spore germination in vitro. This agrees with earlier reports on antimicrobial plant extracts (Akaeze & Aduramigba-Modupe, 2017;Dhaliwal et al, 1990;Enikuomehin, 1998;Giordani et al, 2020). Rice husk extract was the most effective of all the botanicals tested, followed by Azadirachta indica.…”
Section: A Indica D Benthamianus Oryza Sativa Z Zanthoxyloidessupporting
confidence: 92%
See 2 more Smart Citations
“…The presence of antifungal substances in the extracts could be responsible for the observed inhibition of radial growth, as well as possible inhibition of spore germination in vitro. This agrees with earlier reports on antimicrobial plant extracts (Akaeze & Aduramigba-Modupe, 2017;Dhaliwal et al, 1990;Enikuomehin, 1998;Giordani et al, 2020). Rice husk extract was the most effective of all the botanicals tested, followed by Azadirachta indica.…”
Section: A Indica D Benthamianus Oryza Sativa Z Zanthoxyloidessupporting
confidence: 92%
“…This conformed to the observations of Olufolaji and Adeyeye (2002); Olufolaji. and Ojo (2005) and Akaeze and Aduramigba-Modupe (2017) in their studies on the bioassay of some plant extracts on selected fungal pathogens.…”
Section: Inhibitory Effect Of Plant Extracts On Disease Severity and Plant Heightmentioning
confidence: 99%
See 1 more Smart Citation
“…Naing, et al [151] concluded that bacterial strain Paenibacillus ehimensis KWN38 showed high antifungal activity against six tested fungal pathogens belonging to various taxonomic groups; the strain produced volatile antimicrobial the fatty acid chains in the membrane lipid bilayer and alter fluidity and permeability of cell membranes [140]. Akaeze, et al [49] reported that methanol extracts of A. indica at low concentration of 12.5% showed more bioactivity against F. oxysporum lycopersici.…”
Section: Genetic Methods: Use Of Resistant Cultivarsmentioning
confidence: 99%
“…Every 100-gram of raw tomatoes contain 93.59% water, 22 calories, 1.1 g protein, 4.7 g carbohydrates, 13 mg calcium, 27 mg phosphorous, 0.5 mg ferrous, 244 mg potassium, 900 mg vitamin A 0.06 mg thiamine, 0.04 mg riboflavin, 0.7 mg niacin, 23 mg ascorbic acid [29,45]. In addition, the red pigment of the lycopene which tomato fruit contains has attractive interest because the lycopene has high antioxidant ability against oxygen radicals that may cause cancer, aging, arteriosclerosis, etc [11,41,[46][47][48][49][50].…”
Section: Importance and Use Of Tomato Plant: Nutritive Valuementioning
confidence: 99%